2019
DOI: 10.1073/pnas.1819570116
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale determination of spontaneous magnetic reversal in oxide heterostructures

Abstract: Interfaces between transition metal oxides are known to exhibit emerging electronic and magnetic properties. Here we report intriguing magnetic phenomena for La 2/3 Sr 1/3 MnO 3 films on an SrTiO 3 (001) substrate (LSMO/STO), where the interface governs the macroscopic properties of the entire monolithic thin film. The interface is characterized on the atomic level utilizing scanning transmission electron microscopy and electron energy loss spectroscopy (STEM-EELS), and density functional theory (DFT) is emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…As shown in Fig. 8a and 8b, it has been determined from STEM data that only aac 0 (c is perpendicular to the interface) rotation pattern can be responsible for the observed zig-zag oxygen arrangement [126,128]. Second harmonic generation is a technique that probes the electron symmetry at a region of broken symmetry [40].…”
Section: Electronic and Structural Symmetry At The Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 8a and 8b, it has been determined from STEM data that only aac 0 (c is perpendicular to the interface) rotation pattern can be responsible for the observed zig-zag oxygen arrangement [126,128]. Second harmonic generation is a technique that probes the electron symmetry at a region of broken symmetry [40].…”
Section: Electronic and Structural Symmetry At The Interfacementioning
confidence: 99%
“…La0.67Sr0.33 after the third atomic column from the interface. (d) L2,3 ratio and Mn nominal oxidation state as a function of distance from the interface[126]. Adapted from[126]…”
mentioning
confidence: 99%
“…Figure 4 shows a schematic that suggests an explanation for the hysteresis inversion based on the observed triple regions in STEM. The onsets of magnetizations show that FM-1 and FM-2 couple ferromagnetically, while at the interface, antiferromagnetic (AFM) coupling is expected where there is a considerable amount of excess Sr [26,46,47]. At high magnetic fields in the positive direction, all moments are aligned in the direction of the magnetic field.…”
mentioning
confidence: 96%
“…Recently, it has been shown that the interfacial structure coupling together with composition variations near the interface leads to complex magnetic interactions [26]. In fact, the collaborating effects of change in bond geometry and composition are both necessary for observing spontaneous magnetic reversal and inverted hysteresis.…”
mentioning
confidence: 99%
See 1 more Smart Citation